A Maize Glutaredoxin Gene, Abphyl2, Regulates Shoot Meristem Size and Phyllotaxy. Issue 1 (23rd January 2015) - Yang, Fang; Bui, Huyen Thanh; Pautler, Michael; Llaca, Victor; Johnston, Robyn; Lee, Byeong-ha; Kolbe, Allison; Sakai, Hajime; Jackson, David
Abstract : A novel pathway, composed of a glutaredoxin and a TGA transcription factor, regulates shoot apical meristem size independently of CLV-WUS signaling. Abstract: Phyllotaxy describes the geometric arrangement of leaves and is important for plant productivity. Auxin is well known to regulate phyllotactic patterns via PIN1-dependent auxin polar transport, and studies of maize ( Zea mays ) aberrant phyllotaxy1 ( abph1 ) mutants suggest the importance of auxin and cytokinin signaling for control of phyllotaxy. However, whether additional regulators control these patterns is poorly understood. Here, we report a new dominant maize mutant, Aberrant phyllotaxy2 ( Abph2 ), in which the shoot meristems are enlarged and the phyllotactic pattern switches from alternate to decussate. Map-based cloning revealed that the Abph2 mutation was caused by transposition of a glutaredoxin gene, MALE STERILE CONVERTED ANTHER1 ( MSCA1 ), which gained an altered expression pattern in Abph2 mutant embryos. msca1 loss-of-function mutants have reduced meristem size and revealed a novel function of glutaredoxins in meristem growth. In addition, MSCA1 interacts with a TGA transcription factor, FASCIATED EAR4, suggesting a novel regulatory module for regulating shoot meristem size.